The Procedure of Turning A Life Sentence To A Temporary Sentence At The Penitentiary Class 1 Tangerang - Amiludin, Amiludin; Sary Ayu, Fitri Nur; Umara, Undang Prasetya; Razif, Imran Bukhari (Universitas Muhammadiyah Sumatera Utara, 2024)
This study discusses the process of implementing conversion of a life sentence imprisonment to temporary imprisonment at Correctional Institution Class I Tangerang. This research aims to provide an understanding of the procedure of sentence. And identify the obstacles faced in the process implementation. The research method used is normative-empirical law with a qualitative approach. The primary data was sourced from interviews with inmates serving life sentences in the Correctional Institution Class 1 Tangerang and from the perusal of documents concerning the regulations and policies on sentence conversion. The result showed that the sentence conversion involves several stages of administration and assessment which are handled by a number of offices involving various Technical Implementation Units, from the Tangerang Class I Correctional Institution, the Regional Office of the Ministry of Law and Human Rights, and the Directorate General of Corrections. However, the final decision regarding a sentence conversion is in the hands of the President. Some of the faced by prisoners in applying for sentence conversion include a lack of knowledge about the application process, a breach of prison regulations within 5 years preceding the application and the inability to find a guarantor needed for Correctional Assessment. In order to overcome these obstacles, it is suggested to encourage socialization, to support education of inmates about the application process, to provide clear and easily accessible information and to evaluate and simplify the administrative process. Thus, inmates will have a better opportunity to obtain chances for a sentence conversion.